Quality evaluation of citrus varieties based on phytochemical profiles and nutritional properties - Guo, Huan; Zheng, Yin-Jian; Wu, Ding-Tao; Du, Xu; Gao, Hong; Ayyash, Mutamed; Zeng, De-Guang; Li, Hua-Bin; Liu, Hong-Yan; Gan, Ren-You (Frontiers in Nutrition, 2023)
Ten typical citrus varieties were evaluated using statistical methods based on their quality attributes, phytochemicals, and antioxidant properties. Significant differences among different citrus varieties were found. In particular, the total soluble sugar content of Mingrijian was higher than that of other citrus, suggesting its potential for fresh consumption and food processing. Moreover, a total of five flavonoids and nine phenolic acids were identified and quantified. Yuanhong, with a higher content of ascorbic acid and phenolic acids, was considered to be a valuable variety with excellent antioxidant capacity and can be used for value-added processing in the food industry. Principal component analysis and hierarchical cluster heatmap analysis suggested that there were significant differences among the 10 citrus varieties. Correlation analysis confirmed the significant contribution of ascorbic acid and phenolic acids to antioxidant capacity. The results will provide valuable guidance for the identification and further cultivation and utilization of different citrus.